THE ROLE OF GROWTH PROMOTING BACTERIA IN SELENIUM ACCUMULATION BY PLANTS - N. А. Golubkina; A. J. Sokolova; A. V. Sindireva (Овощи России, 2017)
Selenium deficiency is widespread among the human populations  of  different  countries  of  the world  and associating with cardiovascular diseases and cancer that determines the necessity to develop new technology needs to increase selenium accumulation levels by agricultural crops. Besides that, the utilization of selenium containing food supplements, soil and foliar application of selenium salts are the most popular approach to  resolve the selenium deficiency  problem.  At  the same time there is a certain drawback of selenium plant biofortification, which is a low accumulation of the element, and as a result, the possibility of environmental pollution caused the element. The review is devoted to a new direction in improving plant selenium accumulation via utilization of rhizobacteria; their participation in selenium cycle; mechanism of bacteria-selenium-plant interaction; the role of volatile compounds, released by rhizobacteria, on selenium accumulation. The questions that were separately considered were regarding rhizobacteria Microbacterium oxydans extracted from Cardamine hupingshanesis that had an exceptionally high resistance to selenium impact and ability to synthesize selenocystin.